2018
DOI: 10.1002/admi.201800339
|View full text |Cite
|
Sign up to set email alerts
|

2D Materials Beyond Graphene for Metal Halide Perovskite Solar Cells

Abstract: In this Research News, the authors summarize the work that has been done on the utilization of 2D materials beyond graphene in the electron transport layer (ETL) and hole transport layer (HTL) selected of metal halide perovskite solar cells (PSCs). On the one hand, the impact of such materials in the stability of PSCs under operational conditions is impressive. Stabilities for encapsulated PSCs cells under illumination and ambient conditions at maximum power point that retain 80% of their initial performance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In such devices, 2D materials are widely used as in the active (donor) or in various interface/interconnecting layers for exciton generation or charge extraction. [196][197][198][199][200][201][202][203][204] A promising novel donor material should have direct bandgap (1.2-1.6 eV), high absorption coefficient, high carrier mobility, and low exciton binding energy, E B . A low E B is favorable for the efficient separation of photogenerated charge carriers.…”
Section: Energy Conversionmentioning
confidence: 99%
“…In such devices, 2D materials are widely used as in the active (donor) or in various interface/interconnecting layers for exciton generation or charge extraction. [196][197][198][199][200][201][202][203][204] A promising novel donor material should have direct bandgap (1.2-1.6 eV), high absorption coefficient, high carrier mobility, and low exciton binding energy, E B . A low E B is favorable for the efficient separation of photogenerated charge carriers.…”
Section: Energy Conversionmentioning
confidence: 99%
“…[17][18][19] In recent years, two-dimensional (2D) materials, especially graphene, have attracted great attention and have been used in PSCs due to their unique optical and electronic properties. 20,21 To date, CH3NH3PbI3-based regular (n-i-p type) and inverted (p-i-n type) PSC containing graphene oxide (GO) as charge transport layer were reported to achieve PCEs of 18.19% 22 and 13.8% 23 , respectively. Reducing GO has proven an effective method to improve the conductivity of GO and Yeo et al reported the first reduced graphene oxide (rGO)-based inverted CH3NH3PbI3 PSC, which reached a PCE of 10.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of two-dimensional (2D) materials at different sections of perovskite solar cells (PSCs) represents an effective approach to enhance both the power conversion efficiency (PCE) and the lifetime stability of such photovoltaic technology. [1][2][3][4] Meanwhile, the exceptional optoelectronic properties of 2D materials and their compatibility with large-scale, solutionprocessable methods (e.g., roll-to-roll printing techniques) lay the ground for the direct integration of low-cost and flexible photovoltaic devices in emerging smart and multifunctional technologies. [5][6][7][8][9][10][11] The beneficial impact of graphene and related 2D materials in PSCs has been demonstrated both in mesoporous [12][13][14][15][16] and inverted planar structures, [17][18][19] as well as in their corresponding tandem systems.…”
Section: Introductionmentioning
confidence: 99%